Dependence of wind load on air density for highrise buildings. Issue 211 (April 2021) - He, Y.C.; Lin, H.B.; Fu, J.Y.; Chan, P.W.; Zheng, Q.X.; Deng, T.
Abstract: Accurate determination of wind load is of great importance for the wind-resistant design of building structures. Despite the fact that air density varies systematically with altitude, and somewhat less so with barometric pressure, air temperature, and latitude, there is a lack of studies on the dependence of wind load on air density especially for highrise buildings. This article presents a special study on this topic. The dependence of air density on latitude, season and altitude is investigated first, based on meteorological records at several national stations in China. The height-dependence of air density in the inner region of a tropical cyclone (TC) is highlighted, since there is a fast development of highrise buildings in TC-prone areas and TC wind load dominates the design wind loads for such slender wind-sensitive structures. A data-driven model for the height-dependence of TC air density is established. It is shown that the measured TC air density is reduced by 8 % –10% compared with the values recommended in the wind load codes. The dependence of wind load and wind-induced structural response on air density for a supertall building is then analyzed through a combined usage of the proposed TC air density model and wind tunnel testing. Results suggest that the wind load and wind-induced response of the building obtained by considering the height-dependence of air density can be decreased by as much as 12 % compared with those without considering such effects. Thus, more economic wind-resistant designs for highrise buildings may be achieved by taking into account the height-dependence of air density. Highlights: Examined dependence of air density on latitude, altitude and season. Compared measured results with provisions in wind load code. Proposed a profile model of air density in typhoon-prone area. Explored air-density dependence of wind effects on high-rise buildings.